ANALYSIS OF ACCELERATION PROGRAM STRATEGIES IN CREATING OUTSTANDING STUDENTS - Fina Safitri Nasution; Amiruddin Siahaan (International Journal of Cultural and Social Science, 2025)
This research was carried out with the aim of describing the planning and implementation process of the program in accelerated students to create outstanding students and describe student achievements after joining the acceleration program. This research uses a qualitative method with a case study approach that goes through the stages of interview, observation, and documentation. Parties directly involved such as the deputy head of the madrasah for curriculum, the program implementation team, and students became resource persons in the research. The results show that the implementation of the acceleration program carried out by the school to create outstanding students is still in the process of development. The school evaluates and changes every year in the implementation of the program to adapt it to the needs of students and solve problems that arise. So that the implementation of the acceleration program can optimize student achievement in the academic and non-academic fields. The academic achievements of students look quite good judging from the results of the report card and the number of student graduations. In the last 1 year, accelerated student graduation is the entire student enrolled in the program. However, for non-academic achievements, students are still not prominent because the school does not focus on them too much. Students are free to choose where to develop their interests and talents based on the extracurricular programs provided by the school